THE UNITY OF COMMUNITY IN CEMETERY: AN ETHNOGRAPHIC STUDY OF THE ISLAMIC BURIAL RITUALS IN ACEH, INDONESIA - Manan, Abdul; Kamarullah, Kamarullah; Husda, Husaini; Rasyad, Rasyad; Fauzi, Fauzi (Islam Futura, 2024)
Our study portrays burial rituals practiced by Aceh Province, Indonesia, as this ethnic group has distinctive traditions for burying deceased members of society due to the intertwining of cultures and religions in Aceh. The intertwining of the Islamic tenet with the local cultures has constructed the burial rituals in Aceh differently from any Islamic community in Indonesia. To discover the ritual’s distinction as this study’s focus, we explored three aspects of the rituals: processes, meanings, and implications. We integrated a qualitative approach through an ethnographic study by observing three burial rituals and interviewing 45 informants across the province. As a result, the processes covered initial meetings, grave cleansing, ceremonious announcement, feast, and pilgrimage. Regarding the ritual’s meanings, we revealed that the Acehnese people practiced the burial rituals to expect God’s blessing and forgiveness for the deceased, represent gratitude and homage toward the left family, affirm the local customs, and consolidate kinship relations. A for the implication, the series of rituals in burying a dead person in Aceh serves as a way to establish a vertical relationship from people to God, along with a horizontal relationship, from person to person, which contains local wisdom representing the identity of Aceh. The urgency of burial rituals reflects communities’ harmony and adherence to cultural and religious beliefs regardless of any condition.